The Age and Composition of the Martian Crust from NWA 7533 - Humayun, M.; Nemchin, Alexander; Grange, M.; Kennedy, A.; Zanda, B.; Hewins, R.; Lorand, J.; Goepel, C.; Lewin, E.; Pont, S.; Deldicque, D. (WILEY-BLACKWELL, 2013)
NWA 7533 is a pre-Noachian regolith breccia, containing siderophiles consistent with 5% chondritic impactor, 4.44 Ga zircons, and LILE enrichments implying a crustal thickness of 50 km established in the first 100 Ma of martian history.